Human Resource Management and Army Recruiting Analyses of Policy Options - Dertouzos, James N. (RAND Corporation, 2006)
U.S. Army Recruiting Command is faced with the challenge of ensuring that the flow of qualified volunteers is adequate to meet future active-duty accession requirements. This report documents research methods, findings, and policy conclusions from a project analyzing human resource management options for improving recruiting production. It details research designed to develop new insights to help guide future recruiter management policies.